2017
DOI: 10.1089/g4h.2017.0072
|View full text |Cite
|
Sign up to set email alerts
|

Exergames Designed for Older Adults: A Pilot Evaluation on Psychosocial Well-Being

Abstract: The study highlighted the effect of fun and entertainment elements on the psychosocial effect of exergames and called for simpler interactive systems and easier exergame tasks for the older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Exergames have been gradually implemented in rehabilitation [ 37 , 38 ], education [ 39 ], and other fields [ 40 ], and have been widely accepted by a range of populations from children [ 41 , 42 ] to the elderly [ 43 , 44 ]; moreover, positive results were found for individuals with various diseases such as dementia [ 45 ], stroke [ 46 ], Parkinson disease [ 34 ], multiple sclerosis [ 47 ], cystic fibrosis [ 48 ], and cancer [ 49 ]. Recent studies have demonstrated the feasibility, acceptability, and effectiveness of exergaming in improving physical functions such as gait and balance [ 50 ], motion control [ 51 ], and exercise capacity [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exergames have been gradually implemented in rehabilitation [ 37 , 38 ], education [ 39 ], and other fields [ 40 ], and have been widely accepted by a range of populations from children [ 41 , 42 ] to the elderly [ 43 , 44 ]; moreover, positive results were found for individuals with various diseases such as dementia [ 45 ], stroke [ 46 ], Parkinson disease [ 34 ], multiple sclerosis [ 47 ], cystic fibrosis [ 48 ], and cancer [ 49 ]. Recent studies have demonstrated the feasibility, acceptability, and effectiveness of exergaming in improving physical functions such as gait and balance [ 50 ], motion control [ 51 ], and exercise capacity [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…AR can provide a more immersive and fulfilling experience for how people interact and engage in different activities, and allow for personalization and enhanced interactivity. Research has also shown that exercise games, such as our SAS booth, have higher enjoyment and promote sustainable physical activity over traditional interventions (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the use of exergames can be beneficial in restoring balance and reducing the risk and frequency of falls in conventional physiotherapy [9], [13], [17]- [21]. Exergames involve dual-task motor and cognitive activities and may promote improvement in cognitive-motor function, degree of independence and adherence of individuals to therapy [13].…”
Section: Designing Exergames For Older Adultsmentioning
confidence: 99%
“…However, exercise intervention programs that tackle the issue to prevent falls in older non-fallers still have some challenges such as "poor program adherence" and "insufficient exercise intensity" that can compromise the intervention [4], [5]. Playing exergames has been an alternative [6] and suggests that playing video games can keep motivation in intrinsic ways [7] and that older adults could learn how to use technology in the same ways as young people, but the emphasis should be on learning time to familiarize and on positive feedback to avoid the fear of technology [8] , [9]. Authors state that the use of this type of technology may be effective in reducing the risk and incidence of falls in conventional physiotherapeutic treatment [4], [7], [10]- [14].…”
Section: Introductionmentioning
confidence: 99%